Role of miRNA in adult ocular tumorigenesis - Romani, Arianna; Melloni, Elisabetta; Lodi, Giada; Bompan, Francesca; Foschi, Rebecca; Zauli, Enrico; Pozza, Elena; Secchiero, Paola; Zauli, Giorgio; Previati, Maurizio; Voltan, Rebecca (Frontiers in Molecular Biosciences, 2025)
In recent years, cancer research has made huge advances also thanks to the discovery of the role of non-coding RNAs in the control of tumorigenesis, tumor proliferation, migration and metastasis and therefore also in the diagnosis and therapy of tumors. This work aims to review the most recent literature involving the study of miRNAs in ocular tumors affecting adult patients. We will introduce the role of miRNAs in tumorigenesis, and we will focus on summarizing the studies on uveal intraocular melanomas in which a role of microRNAs has been demonstrated. Similarly, we will also cover observations on miRNAs and eyelid cancers, especially sebaceous gland carcinoma, and cancers of the conjunctiva and the retina, excluding retinoblastoma which is typically a pediatric-onset tumor. We will summarize specific miRNAs that could be considered as diagnostic molecules or as therapeutic targets against some ocular cancer diseases, indicating their potentialities and limitations, considering also their administration as nanomedicine for the eye.